2016
DOI: 10.1080/19443994.2015.1076351
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradation of 2,4-dichlorophenol by Bacillus endophyticus strain: optimization of experimental parameters using response surface methodology and kinetic study

Abstract: A B S T R A C TIn the present study, the optimization of various experimental parameters, i.e. pH, temperature (˚C), inoculum size % (v/v) and ammonium sulphate concentration (g L −1 ) at different levels were carried out to enhance the 2,4-dichlorophenol (2,4-DCP) degradation by newly isolated Bacillus endophyticus strain CP1R. The central composite design of response surface methodology (RSM) was applied for the optimization process. It was observed that the maximum biodegradation efficiency of 100% was achi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 20 publications
(26 reference statements)
0
13
0
Order By: Relevance
“…These genera can often be detected in water treatment. Among the dominant bacteria detected in this study, Bacillus were reported to have the capability to degrade chlorophenols as carbon and energy sources (Karn, Chakrabarty, & Sudhakara Reddy, ; Karn & Reddy, ; Patel & Kumar, ). Moreover, Bacillus has the ability to degrade phenol (Banerjee & Ghoshal, , ).…”
Section: Resultsmentioning
confidence: 95%
“…These genera can often be detected in water treatment. Among the dominant bacteria detected in this study, Bacillus were reported to have the capability to degrade chlorophenols as carbon and energy sources (Karn, Chakrabarty, & Sudhakara Reddy, ; Karn & Reddy, ; Patel & Kumar, ). Moreover, Bacillus has the ability to degrade phenol (Banerjee & Ghoshal, , ).…”
Section: Resultsmentioning
confidence: 95%
“…There are several methods for CP removal, including biodegradation, 6 chemical reduction, 7,8 and electrocatalytic hydrogenolysis (ECH). [9][10][11] ECH is considered an environmentally-friendly and highly-efficient technology in the dechlorination of CPs.…”
Section: Introductionmentioning
confidence: 99%
“…These genera can often be detected in water treatment. Among the dominant bacteria detected in this study, Bacillus were reported to have the capability to degrade chlorophenols as carbon and energy sources (Karn, Chakrabarty, & Sudhakara Reddy, 2010;Karn & Reddy, 2013;Patel & Kumar, 2016). Moreover, Bacillus has the ability to degrade phenol (Banerjee & Ghoshal, 2010.…”
Section: Research Articlementioning
confidence: 78%